Vocational High School Teachers’ Perception of Teaching Modul (Modul Ajar) in Merdeka Curriculum - Arum Adiningtyas; Endah Yulia Rahayu (Journal of Applied Linguistics and English Education, 2023)
This study examines vocational high school teachers' grasp of the Merdeka curriculum, particularly Modul Ajar, as “Merdeka” curriculum modifications. The Merdeka curriculum framework, block learning method, and learning device components, which guide the teacher, have changed. With this research, the author understands the Merdeka curriculum better. This study covers education challenges, particularly in the Merdeka curriculum. This qualitative study examined vocational high school EFL instructors' views on Merdeka curriculum implementation. Vocational high school English teachers were interviewed and transcribed. Reduction analysis followed. This study found that Merdeka's extracurricular learning group is divided into two groups: a mandatory general group to form student norms and a significant group assigned to each student based on their expertise program to prepare them for the workforce. The Pancasila Student Profile outlines the teacher's hopes for students in the Merdeka curriculum. Implementing the learning system requires a block system. The teacher can customize the Teaching Module to fit their Learning Outcomes.